Análisis del rendimiento del cultivo de quinua (Chenopodium quinua Willdenow) en el Ecuador - Azú Chong, Liliana Leonor (2023)
In reference to the case study based on the analysis of the yield of the quinua crop in Ecuador, the analysis of the yield of quinua production in Ecuador is fundamental to understand the current panorama of this crop and explore the possibilities for improvement in terms of quality, productivity and sustainability, the general objective was to analyze the yield of quinua in the country. The study was based on a descriptive study with a bibliographic-documentary approach. In reference to the results obtained in the case study on the analysis of quinua yields in Ecuador, a series of important and key findings were made, such as the considerable variability in the level of quinua yields throughout the country, especially in the highlands region, due to factors such as climate, soil, altitude, humidity, and agricultural skills that have a positive impact on the production of this crop. In conclusion, it has been identified that the main problems affecting the productivity of the quinua crop in Ecuador are due to climate conditions, the lack of focus to carry out the relevant control of diseases and pests that affect the crops.